2018
DOI: 10.1021/acscatal.8b02616
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Study of the Reaction Mechanism of the Dehydratase Domain from Mammalian Fatty Acid Synthase

Abstract: Dehydratase (DH) is a catalytic domain of the mammalian fatty acid synthase (mFAS), a multidomain enzyme with seven different active sites that work in tandem to carry out the biosynthesis of palmitic acid for de novo lipogenesis. DH catalyzes the dehydration of the β-hydroxyacyl to an α,β-unsaturated acyl intermediate. We have conducted hybrid QM/MM calculations to clarify the catalytic mechanism for the DH domain at the ONIOM­(DFT/Amber) level of theory. The results have shown that the dehydration step occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 75 publications
(139 reference statements)
4
57
0
Order By: Relevance
“…The oxyanion hole stabilization has also been quantified in other studies that focused on enzymes such as subtilisin, thiolase, ketosteroid isomerase, dehydratase, trypsin and transferase . These studies reported an oxyanion hole‐mediated stabilization of transition‐states of 4–6 kcal ⋅ mol −1 , which is lower than the 7–11 kcal ⋅ mol −1 presented in the current work.…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…The oxyanion hole stabilization has also been quantified in other studies that focused on enzymes such as subtilisin, thiolase, ketosteroid isomerase, dehydratase, trypsin and transferase . These studies reported an oxyanion hole‐mediated stabilization of transition‐states of 4–6 kcal ⋅ mol −1 , which is lower than the 7–11 kcal ⋅ mol −1 presented in the current work.…”
Section: Resultsmentioning
confidence: 43%
“…Indeed, this 7–11 kcal ⋅ mol −1 energy range lays close to the 11.1 kcal ⋅ mol −1 value reported by Medina et al . after performing a double replacement protocol …”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the catalytic mechanism, hybrid QM/MM procedure was applied as previously reported in similar systems [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The QM region includes Cys18, His22 of the seven chains and Glu25 faced into the hydrophobic channel of the CC-Hept-Cys-His-Glu and three water molecules (w1, w2 and w3) engaged in a hydrogen bonds network (see Figure 4 ) both with each other and with the catalytic triad ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to quantify entropic contributions, the Grimme’s procedure [ 50 ] was employed as reported in other works [ 14 , 15 , 16 ]. According to this method, only vibrational temperatures higher than 100 K are taken into account to calculate TΔS contribution using the harmonic oscillator/rigid rotor/particle in a box formalism.…”
Section: Methodsmentioning
confidence: 99%
“…Only vibrational temperatures larger than 100 K have been accounted for, during the calculation of the entropy contribution, according to a validated procedure, [49] already successfully used in other works. [50][51][52] The final energy profiles were obtained adding the Zero Point Energy, the empirical D3-dispersion correction [47] and entropy contributions, as reported in Table S1.…”
Section: Methodsmentioning
confidence: 99%